The Influence of Content Frequency and Content Quality on Purchase Decision through Brand Awareness - Erislan Erislan (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Digital marketing is currently experiencing rapid growth, particularly in content on social media and online platforms, making understanding content strategy crucial for brands in influencing consumer behavior. This study aims to investigate the influence of two key content attributes, namely content frequency and content quality, on consumer purchase decisions, with an emphasis on the mediating function of brand awareness. Using a quantitative approach and secondary data from ten peer-reviewed journals, this study applies Structural Equation Modeling (SEM) to analyze the relationship between the variables. The findings indicate that both content frequency and content quality have a positive effect on brand awareness, with content quality having a stronger influence. Brand awareness significantly increases the influence of content strategy on purchase decisions, serving as a crucial mediator. While content attributes can directly influence purchase decisions, the indirect influence through brand awareness is more substantial. This study provides valuable insights for marketers, recommending a balanced approach that prioritizes quality content while maintaining an optimal posting frequency, and contributes to the digital content marketing literature.